The Combination of Immune Checkpoint Blockade and Angiogenesis Inhibitors in the Treatment of Advanced Non-Small Cell Lung Cancer - Ren, Sijia; Xiong, Xinxin; You, Hua; Shen, Jianfei; Zhou, Penghui (Frontiers in Immunology, 2021)
Immune checkpoint blockade (ICB) has become a standard treatment for non-small cell lung cancer (NSCLC). However, most patients with NSCLC do not benefit from these treatments. Abnormal vasculature is a hallmark of most solid tumors and is involved in tumor immune escape. These abnormalities stem from the increase in the expression of vascular endothelial growth factor (VEGF), which regulates the function and migration of immune cells. Anti-angiogenic agents can normalize blood vessels, and thus transforming the tumor microenvironment from immunosuppressive to immune-supportive by increasing the infiltration and activation of immune cells. Thus, the combination of immunotherapy with anti-angiogenesis is a promising strategy for cancer treatment. This review outlines the current understanding of the mechanisms of VEGF/VEGFR signaling in tumor immune escape and progression, and summarized the preclinical studies and current clinical data of the combination of ICB and anti-angiogenic drugs in the treatment of advanced NSCLC.